Performance Comparison Of Intelligent Tuning Methods Using Pid-Afcga And Pid-Afcpso In Attenuating The Vibration Of The Suspended Handle Model - Choo, Kinn (Universiti Sains Malaysia, 2021)
In this study, the performance of different control schemes in attenuating the vibration of the suspended handle model is investigated. Prolonged exposure to the undesirable vibration of the power tools can cause detrimental effect to the worker health and resulted in sickness like hand-arm vibration syndrome (HAVS). An effective vibration control system is necessary to suppress the vibration of the power tools, whereby vibration control through active force control (AFC) is proven to be a feasible method from the previous research. However, AFC requires proper tuning process to optimally attenuate the vibration. Thus, several tuning methods such as crude approximation (CA), genetic algorithm (GA) and particle swarm optimization (PSO) are implemented and compared based on the performance of the suspended handle model under different vibration. From the results, the AFC schemes are very effective in attenuating the vibration compared to passive system and proportional-integral-derivative (PID) controller. Among the AFC schemes, PSO tuning method has the best performance even though under the influence of different disturbances. AFC with intelligent tuning method is a promising solution for the vibration control especially in power tool application.